Chewing lice (Phthiraptera: Amblycera and Ischnocera) from wild birds in southern Vietnam, with descriptions of two new species - Najer, Tomas; Sychra, Oldrich; Kounek, Filip; Papousek, Ivo; Hung, Nguyen Manh (Zootaxa, 2014)
A total of 239 individuals of 50 bird species were examined for chewing lice (Insecta: Phthiraptera) in southern Vietnam. Fifty-six birds of 20 species were parasitised by 15 species of lice belonging to 10 genera from two suborders, Amblycera: Menacanthus, Meromenopon, Myrsidea, and Ischnocera: Alcedoecus, Brueelia, Cuculicola, Meropoecus, Penenirmus, Philopteroides and Philopterus. Thirteen louse samples from Passeriformes were identified to genus only because they contain inadequate material. A total of 29 host-louse associations were found, of which nine are new, including: (1) two new species of the genus Brueelia, which are described and named in this paper: Brueelia binhchauensis from Megalaima lineata (Vieillot, 1816) (Piciformes: Megalaimidae), and Brueelia malacocincla from Malacocincla abbotti Blyth, 1845 (Passeriformes: Pellorneidae); (2) first records of lice from Cyornis hainanus (Ogilvie-Grant, 1900); and (3) the first record of Myrsidea claytoni Hellenthal & Price, 2003 from Cymbirhynchus macrorhynchos (Gmelin, 1788) (Passeriformes: Eurylaimidae), here regarded as a case of natural host-switching. A portion of the mitochondrial cytochrome oxidase I (COI) gene for some species of chewing lice was sequenced in order to assess their genetic divergences.